Inflammatory tissue reactions around aseptically loose cemented hip prostheses: A retrieval study of the Spectron EF stem with Reflection All‐Poly acetabular cup. Issue 7 (31st January 2022) - Wolf, Susann; Johannessen, Anne Christine; Ellison, Peter; Furnes, Ove; Hallan, Geir; Rogg, Katharina; Skarstein, Kathrine; Høl, Paul Johan
Abstract: The cemented Spectron EF stem in combination with the cemented non‐crosslinked Reflection All‐Poly cup showed a high rate of mid‐term aseptic loosening. However, the failure mechanisms are not fully known. We assessed the inflammatory tissue reactions and wear particles in periprosthetic tissues, implant wear and blood metal ion levels in 28 patients with failed implants. Histological analysis showed a macrophage pre‐dominant pattern with randomly distributed lymphocytes, with various amounts of neutrophils and giant cells. The number of different cell types in the tissue samples from patients in the cup group and in the stem group was similar. Wear particles, mainly ZrO2, CoCrMo, and polyethylene particles of different sizes and shapes, were associated with macrophages/giant cells, and total particle load/mm 2 was higher in cases of stem loosening. The Spectron EF stems were heavily worn, abraded, and polished. Stem abrasion correlated with metal ion concentrations in blood. The median polyethylene wear rate of the Reflection cups was 0.23 mm/year. The high proximal roughness of the Spectron EF stem resulted in excessive cement wear during loosening. The resulting inflammatory tissue responses to the degradation products both from the cup and the stem led to massive osteolysis and subsequent implant loosening.